Postoperative infectious complications in patients undergoing holmium laser enucleation of the prostate: Risk factors and microbiological analysis. (14th June 2016) - Kikuchi, Mina; Kameyama, Koji; Yasuda, Mitsuru; Yokoi, Shigeaki; Deguchi, Takashi; Miwa, Kosei
Abstract : Objectives: To examine the incidence of postoperative bacteriuria and febrile complications, and to investigate bacterial strains in the urine of patients undergoing holmium laser enucleation of the prostate. Methods: We retrospectively analyzed 190 evaluable patients treated with holmium laser enucleation of the prostate at the Gifu University Hospital, Gifu, Japan, between September 2005 and May 2014. All patients presented with lower urinary tract symptoms as a result of benign prostatic hyperplasia. We also evaluated the causative bacteria and compared the findings with the results of preoperative urine cultures. We analyzed the relationship between the emergence of postoperative febrile complications, antibiotic prophylaxis, patient background and surgical procedure. Results: The frequency of bacterial isolation in preoperative and postoperative urine cultures was 41% and 23%, respectively. Preoperatively, Enterococcus faecalis was the most frequently cultured bacteria, second was methicillin‐resistant Staphylococcus epidermidis, and third was Escherichia coli . Postoperatively, Enterococcus faecalis was still the most frequently cultured bacteria, whereas the second was Escherichia coli . Risk factors for postoperative bacteriuria were evaluated. Multivariate analysis showed that the rate of postoperative bacteriuria in patients who had taken dutasteride preoperatively was significantly lower than that in the other patients. Risk factors for febrile complications could not be identified. Conclusions: The use of perioperative prophylactic antibacterial agents for holmium laser enucleation of the prostate keeps the rate of postoperative infectious complications low. Dutasteride treatment administered before surgery might reduce the risk of postoperative bacteriuria.